Applications of GIS in Flood Control and Crises Management Using Different Sources of DEMs in Al Arish, Sinai, Egypt - Ahmed Amin; Ahmed El-Hattab; Mohamed El Bastawesy; Ahmed Sharawi; Marwa Azzam (Port Said Engineering Research Journal, 2016)
The aim of this research is to provide an approach to identify the potential routes of water flood in the study area as well as its relevant area of containment (Al Arish, North Sinai, Egypt). The outcomes of the research shall help in early warning to avoid catastrophic damages to the community area and consequent fatalities, destruction of infrastructures and property losses. To obtain the best accuracy in this research the issue of flood hazard, vulnerability and risk mapping will be displayed from the perspective of different mapping scale in a GIS environment. GIS is extensively used to assemble information from different maps, remote sensing images and Digital Elevation Models (DEMs). However, in the current research, two Semi- Hydraulic Models (since Al-Arish area does not form a complete drainage basin, but it is considered as the outlet of drainage basin for Wadi Al-Arish which is located in the middle of Sinai Peninsula, so, time zones and hydraulic structures design are not included) are presented, namely: Interactive-GIS Based Model and Automated- GIS based Model.